A Retrospective View on Designation of Origin Labeled Foods in Europe. Issue 3 (3rd July 2017) - Krystallis, Athanasios; Chrysochou, Polymeros; Perrea, Toula; Tzagarakis, Nikolaos
ABSTRACT: In the emergence of ethically conscious consumer segments across Europe, the expectation was that foods with a designation of origin–label (DOL) would make a production system of similar logic. Past analysis of the registration history of DOLs showed that the take-up of this European Union (EU) food quality scheme was concentrated in the south, which was attributed to specific food supply-and-demand conditions prevalent in that part of Europe. The authors shed light on DOL product distribution and examine its evolution during a 14-year period (2001–2014). DOLs remain a quality differentiation scheme predominantly for the southern EU agrifood industry. However, the less restrictive requirements for protected geographical indication certification make it a much more popular DOL in northern EU. To promote its food quality policy, the EU must approach the two DOL types differently, as they have a different growth potential among EU countries. DOLs' specialization in categories with expertise accumulated in specific EU areas can become a DOL promoter across all of Europe.